2016
DOI: 10.5714/cl.2016.20.076
|View full text |Cite
|
Sign up to set email alerts
|

Biologically activated graphite fiber electrode for autotrophic acetate production from CO2in a bioelectrochemical system

Abstract: Recently, microbial electrosynthesis (MESs) has been highlighted for the purpose of biological CO 2 reduction with simultaneous production of intermediates and value-added chemicals. The bioelectrochemical system (BES), which employs microorganisms and a bacterial community as a biocatalyst, has been developed to convert CO 2 , a greenhouse gas, into liquid biofuels, such as ethanol and butanol, as well as platform chemicals [1]. Several bacterial species, called cathodophilic microorganisms (e.g., Sporomusa o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…However, microorganisms only attached sporadically to unmodified carbon felt in that study. Similarly, Aryal et al (2016) and Im et al (2016) showed only few microorganisms attaching to the surface of unmodified carbon felt, while a more developed biofilm covered the surface of graphenemodified carbon felt (Aryal et al, 2016). All these studies were carried out in H-type reactors with magnetic stirring.…”
Section: Resultsmentioning
confidence: 99%
“…However, microorganisms only attached sporadically to unmodified carbon felt in that study. Similarly, Aryal et al (2016) and Im et al (2016) showed only few microorganisms attaching to the surface of unmodified carbon felt, while a more developed biofilm covered the surface of graphenemodified carbon felt (Aryal et al, 2016). All these studies were carried out in H-type reactors with magnetic stirring.…”
Section: Resultsmentioning
confidence: 99%
“…The interaction of the microbe–electrode has been highlighted in light of the development of advanced electrochemically driven bioprocesses, such as MFCs and microbial electrosynthesis . The exchange of respiratory electrons through the extracellular electron transport pathway may regulate the internal cellular metabolism, and probably affect the titer and yield of the target biochemicals .…”
Section: Resultsmentioning
confidence: 99%
“…The coulombic efficiencies of EF are generally low (1-38 %) using fermentable substrates, such as glycerol, glucose, sucrose, and lactose [1] .This result can be compared with another representative cathodic conversiono fC O 2 ,m icrobial electrosynthesis, with 70-100 %c oulombic efficiency in BES, which suggests that most of the electrons transferred from the cathode are delivered to CO 2 reduction by bacteria. [30] The significant difference in electron recoveryi so wing to the different redox levels of the starting feedstock (glycerol vs. CO 2 ). In the glycerol EF, electron transfer by the electrode affects the intracellular redox balance and triggersarebalance of the metabolic flux by expression/depression of the involved enzymes.T hism etabolic "butterfly effect" could be applied to various bioconversions for the reduction/oxidation of feedstock using not only the electrochemically actives train in EF but also conventionalf ermentation using ar ange of industrially available strains.…”
Section: Discussionmentioning
confidence: 99%